VD_FINDINFO HC / 2016 / 697 vom 5. August 2016 - VD Tribunal cantonal (2016)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 163 CC, 176 al. 1 ch. 1 CC, 179 al. 1 CC, 272 CPC (CH)